Particle Swarm Optimization for the Path Loss Reduction in Suburban and Rural Area - Messaoud Garah; Houcine Oudira; Lotfi Djouane; Nazih Hamdiken (Institute of Advanced Engineering and Science, 2017)
In the present work, a precise optimization method is proposed for tuning the parameters of the COST231 model to improve its accuracy in the path loss propagation prediction. The Particle Swarm Optimization is used to tune the model parameters. The predictions of the tuned model are compared with the most popular models. The performance criteria selected for the comparison of various empirical path loss models is the Root Mean Square Error (RMSE). The RMSE between the actual and predicted data are calculated for various path loss models. It turned out that the tuned COST 231 model outperforms the other studied models.